Kebijakan Penanggulangan Bencana: Model Kesiapsiagaan Bencana Berbasis Sekolah/ Madrasah di Provinsi Jawa Barat - Nanang Suparman (Jurnal Public Policy, 2021)
West java is an area that has the potential for very complex disasters. Based on the data release  the regional disaster management agency there have 6,607 disasters in the period 2015-2019, natural disasters in west jawa including earthquakes, tsunami, landslide, flash floods, and so forth. So that, a guidelines for disaster-preparedeness schools is important to avoid school from any kind of disasters. This study  aims to find out and analysis model disaster-preparedeness schools in west java province and relation of disasters handling. This research using a qualitative method. Data collection, interviews with informants and collection of documents related to the policy guidelines for safe schools from disasters. Data analysis teachniques used are from the miles and Huberman models which include data reduction, data presentation, verification and conclusion. The results of this research indicate that the implementation model of disaster preparedness school policy as a whole has fulfilled the rules of disaster mitigation management by implementing regulations and procedures from both the central and regional levels. However, judging from the basic measures, objectives, policy resources and communication between organizations have not gone well so it has not been able to cope with the negative impacts of disasters in the school environment.